KERJASAMA JEPANG DENGAN NEGARA-NEGARA KAWASAN KEPULAUAN PASIFIK DALAM MENANGANI PENGELOLAAN LIMBAH PADAT DI KEPULAUAN PASIFIK PERIODE 2011-2016 - Gissela Enno H. E. (2022)
The purpose of this study is to find out how the J-PRISM collaboration series flows and how it impacts on solid waste management in the Pacific Islands. This study uses the theory of international cooperation, international organizations, foreign aid, and the concept of environmentalism in analyzing the topics to be studied. The Pacific Islands region is one of the regions located in the Pacific Ocean. Surrounded by vast waters with great distances from each other, making the Pacific Islands region difficult to reach and can be said to be geographically isolated. Geographical limitations cause the region to be said to be a developing country with inadequate infrastructure to develop its country. One of the problems faced by the region is that the Solid Waste Management in the area is not yet optimal, making the area need assistance from foreign countries in order to fix the problems faced. Japan as one of the largest donor countries in the world provides assistance in the form of technical assistance as stated in the J-PRISM collaboration or Japanese Technical Cooperation for Promotion of Regional Initiative on Solid Waste Management in Pacific Island.